Increasing Sexual Violence by Children as A Reflection of The Improvement of Sex Education in Indonesia - Ramadhana Satria Tamtama; K Kuswardani (Proceeding International Conference Restructuring and Transforming Law, 2023)
The general opinion that sex education is taboo because sex education is not based on religious teachings assumes that sex education is the same as educating men and women about sexual relations. The aim of this research is to describe the increase in sexual violence against children due to a lack of sex education among children. Because this study is an empirical-legal study, the information needed is secondary information in the form of legal documents and primary information in the form of information from stakeholders, especially those related to children's problems. The results of the research show that society's perception of the taboo on sex education has a significant impact on the increase in sexual violence against children. Because stakeholders need to pay attention, especially in the education sector, to teaching about correct sexual education based on religion.